Adult Attachment Patterns Modify the Association Between Social Support and Psychological Distress - Kizuki, Masashi; Fujiwara, Takeo (Frontiers in Public Health, 2018)
Introduction: Social support is an important protective factor for psychological distress, and adult attachment patterns—which are the basis of human relationships—may modify the association between social support and psychological distress. The objective of this study was to investigate whether adult attachment patterns modify the association between social support and psychological distress. Methods: A commercial online survey service was used to collect data from 1648 men and women of 30–69 years of age in Japan. We assessed the association between psychological distress, as measured by the Kessler Psychological Distress Scale (K6), and stratified it by adult attachment patterns using multiple linear models. Adjustments were made for age, sex, presence of a spouse and child in the household, level of education, employment, and household income. Results: There was a significant interaction effect between social support score and a dismissing attachment pattern on psychological distress (p=0.015); social support was associated with reduced level of psychological distress only in participants with a secure attachment pattern (β:-0.86, 95% CI: -1.56 to -0.16), whereas the point estimate was of opposite sign in participants with a dismissing attachment pattern (β:1.02, 95% CI: -0.32 to 2.37). Conclusions: Higher social support reduced the risk of distress among participants with secure attachment. On the contrary, social support can be harmful for those with a dismissing attachment pattern. Our results suggest that further assessment of adult attachment patterns is needed to maximize the positive effects of social support to prevent psychological distress.